1996
DOI: 10.3109/10611869608996824
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Modification: Relevance of Improved Methodology to Tumour Targeting

Abstract: Of all the polymers applied to molecule altering structural chemistry, polyethylene glycol (PEG) modification has numerous benefits and relatively few drawbacks. PEG is now increasingly being applied to the problems of tumour targeting, both in the context of the passive targeting of PEG-liposomes and in active targeting strategies using PEGylated anti-tumour antibodies. PEG can also serve as a useful linker molecule between targeting moieties and other agents, including cytotoxic or imaging agents and targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 63 publications
0
29
0
1
Order By: Relevance
“…Conjugation of the EGF or the OVA to the terminal of the PEG chains on the GemC18-NPs was likely responsible for the shorter half-life observed. It is known that the ability of the PEG to extend the blood circulation time of a drug carrier is related to parameters such as the amount and the molecular weight of the PEG [32]. Therefore, further future research efforts are underway to examine the feasibility of extending the half-life of the EGF-GemC18-NPs by increasing the amount of PEG(2000) in the formulation or using longer PEG molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Conjugation of the EGF or the OVA to the terminal of the PEG chains on the GemC18-NPs was likely responsible for the shorter half-life observed. It is known that the ability of the PEG to extend the blood circulation time of a drug carrier is related to parameters such as the amount and the molecular weight of the PEG [32]. Therefore, further future research efforts are underway to examine the feasibility of extending the half-life of the EGF-GemC18-NPs by increasing the amount of PEG(2000) in the formulation or using longer PEG molecules.…”
Section: Resultsmentioning
confidence: 99%
“…In this instance, the trifunctional PEO core contributes most of the mass of the system. The advantages of using a star-PEO also include its contribution to biocompatibility and water solubility (40), without jeopardizing the polydispersity of the system, since star-PEO molecules with low polydispersity indices (PDI < 1.1) are commercially available. On the other hand, the [G-2] polyester dendrons of III provide the multivalency necessary for drug attachment.…”
Section: Resultsmentioning
confidence: 99%
“…It has for instance been demonstrated that poly(ethylene glycol) (PEG) coatings prolong considerably the circulation time of polymeric nanoparticles in the blood stream. 25 Finally, the presence of such long stabilizing polymer chains at their surface may impart nano-/microgels with high stability and prevent them from aggregation.…”
Section: Introductionmentioning
confidence: 99%